FEATURES OF THE FORMATION OF VALUE ORIENTATIONS OF OLDER ADOLESCENTS - Щебельська, О.А. (SWorldJournal, 2022)
The formation of the system of the valuable orientations of the personality acquires the special meanings in adolescence, because with this period of ontogenesis scientists associate the origin of the necessary level of the development of the valuable ori